Portuguese emigration Factbook 2017 - Pires, Rui Pena (2018)
In 2016, the decrease in Portuguese emigration was accelerated, with about 100 thousand individuals leaving the country. The review of the statistical series estimated by the Observatory on total emigration points to the existence of a peak of emigration in 2013, higher than the one estimated so far, of around 120,000 outflows, as well as a progressive slower descent, in 2014 and 2015, to values around 110 thousand exits.